2014
DOI: 10.1177/0146167214521467
|View full text |Cite
|
Sign up to set email alerts
|

Mating Motives and Concerns About Being Misidentified as Gay or Lesbian

Abstract: Recent research has demonstrated that concerns about being misidentified as gay or lesbian lead to the avoidance of gay men and lesbians. Because being misidentified as gay/lesbian can result in the loss of heterosexual people's mating opportunities, we predicted that the activation of mating motives would heighten concerns among some heterosexuals about being misidentified as gay/lesbian. To combat such misidentification, we argued that heterosexuals would express antipathy toward and avoid contact with gay/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Gender was included as a predictor as there is some precedent that men tend to experience higher levels of social contagion concerns than women (e.g., Buck et al, 2013;Plant et al, 2014). There was a significant effect of perceptions of peer prejudice on contagion scores, B = .34, SE = .072, t(115) = 4.48, p < .001, with perceptions of greater peer prejudice being associated with greater contagion concerns for the individual.…”
Section: Resultsmentioning
confidence: 99%
“…Gender was included as a predictor as there is some precedent that men tend to experience higher levels of social contagion concerns than women (e.g., Buck et al, 2013;Plant et al, 2014). There was a significant effect of perceptions of peer prejudice on contagion scores, B = .34, SE = .072, t(115) = 4.48, p < .001, with perceptions of greater peer prejudice being associated with greater contagion concerns for the individual.…”
Section: Resultsmentioning
confidence: 99%
“…In order to address this problem, researchers have traditionally focused on reducing heterosexuals' sexual prejudice (Paluck & Green, 2009). However, recent work has revealed that heterosexuals' contagion concerns contribute to the derogation and avoidance of gay and lesbian individuals (Buck et al, 2013;Plant et al, 2014). Thus, reducing contagion concerns among heterosexuals is a critical part of decreasing the negativity that gay and lesbian individuals face.…”
Section: Discussionmentioning
confidence: 99%
“…Although correlated with traditional sexual prejudice (typically around r = .50), contagion concerns independently contribute to negative responses toward gay men and lesbians. For example, high levels of contagion concerns among heterosexuals lead to heightened interorientation anxiety and avoidance, as well as the denigration of gay men and lesbians (Buck et al, 2013;Plant et al, 2014). Importantly, contagion concerns predict anxious and avoidant responses toward gay men and lesbians even when controlling for sexual prejudice and sexual prejudice does not moderate the effect of contagion concerns on these responses (Buck et al, 2013).…”
Section: Contagion Concerns and Moral Sexual Prejudicementioning
confidence: 99%
See 1 more Smart Citation
“…The participants' accounts of avoidance attests to the avoidance strategy that many gay men fearful of homophobic violence engage in (Almeida, Johnson, Corliss, Molnar and Azrael 2009;Icard et al 2015;Jacques 2014;Plant, Zielaskowski and Buck 2014;Skinta, Brandrett, Schenk, Wells and Dilley 2013). Strategies of avoidance of avowed physical spaces or social spaces where one's sexuality is considered problematic can be read as a survival strategy that enables the individual to maintain a sense of well-being, both physically and mentally.…”
Section: Survival Strategies Avoidancementioning
confidence: 98%